Acarbose treatment affects the serum levels of inflammatory cytokines and the gut content of bifidobacteria in Chinese patients with type 2 diabetes mellitus 阿卡波糖对中国2型糖尿病患者炎症因子及粪便双歧杆菌水平的作用. (15th January 2015) - Su, Benli; Liu, Haixia; Li, Jing; Sunli, Yongjuan; Liu, Ben; Liu, Dandan; Zhang, Ping; Meng, Xiuxiang
Abstract: Background: The effects of acarbose add‐on therapy on gut microbiota and inflammatory cytokines were investigated in Chinese patients with type 2 diabetes mellitus (DM). Methods: Ninety‐five DM patients were randomly allocated to two groups: 59 to Group A who received antidiabetic treatment that included acarbose 150 mg/day, and 36 to Group B who received similar treatment to Group A but without acarbose. Forty‐five healthy volunteers were selected as a control group. Serum concentrations of inflammatory cytokines were determined by ELISA, and the contents of 16S rDNA of gut bacteria were determined by real‐time quantitative polymerase chain reaction. General linear analysis for repeated measurements was used to analyze trend differences between the two diabetic groups. Results: After 4 weeks of antidiabetic treatment, the gut contents of Bifidobacterium longum and Enterococcus faecalis were significantly increased in both diabetes groups. The increase of Bifidobacterium longum ( P  = 0.004) and the decrease of lipopolysaccharides (LPS) ( P  < 0.001) and prothrombin activator inhibitor‐1 ( P  = 0.003) were more significant in Group A. Decreases of monocyte chemoattractant protein‐1 and LPS were more significant in patients whose HbA1c decrease was ≥1%, but there were no significant differences in the changes of other cytokines and gut bacteria between patients with HbA1c <7% and ≥7%. Pearson correlation analysis showed that changes of Enterococcus faecalis were negatively correlated with LPS, while multiple linear regression analysis showed a positive correlation of Bifidobacterium longum with acarbose treatment and the high‐density lipoprotein cholesterol concentration. Conclusions: Acarbose treatment can increase the content of gut Bifidobacterium longum in type 2 diabetes mellitus patients and decrease some inflammatory cytokines independently of its antihyperglycemic effects.